OFR-107-81 Proceedings Of The Fourth WVU Conference On Coal Mine Electrotechnology August 2-4, 1978 (The National Institute for Occupational Safety and Health (NIOSH), 1978)
A compilation of papers presented at the Fourth WVU Conference on Coal Mine Electrotechnology in Morgantown, West Virginia, on August 2-4, 1978. Papers cover areas of electric power, electronic communications, detection and location of trapped miners, and electronic sensors and monitoring systems.